Toxocarasis and the Epilepsy as Clinical Process in Childhood - Vitorino, Aline M.; Aidar, Naira B.; Gonzatti, João V. F.; Guerra, Carollyne R.; Magalhães, Alissa A.; Ferraz, Gabriela M.; Pio, Giovanni P.; Maior, Isabela M.S.; Junior, Juscelino P.; Costa, Larissa P.; Dib, Luisa C.; Cammerer, Eduardo M. (International Journal of Innovative Research in Medical Science, 2022)
The Helminths are still a highly prevalent cause of disease in the world, especially toxocariasis, which results from the infection of Toxocara canis and Toxocara cati. The infection by these parasites occurs accidentally, leading the human being into becoming intermediate hosts of the life cycle. Toxocariasis can present itself in different ways, according to the place where the larva is lodged. This review evaluated epilepsy as an outcome of toxocariasis in pediatric patients. The bibliographic review of the scientific literature was carried out in the library of the Centro Universitário do Planalto Central Professor Apparecido dos Santos (UNICEPLAC), as well as in the PUBMED, MEDLINE, LILACS and COCHRANE databases. Articles in English, Portuguese and Spanish were considered, without date restriction. The course of neurological symptoms results from post-treatment complications, due to the direct presence of the larva in the Central Nervous System (CNS) and/or tissue inflammation, with the outcome of focal (related to granulomas) or generalized (associated with immunological reaction) seizures. Other common manifestations are sleep and behavioral disorders or meningoencephalitis with different prognosis. Laboratory and imaging tests, such as computed tomography and nuclear magnetic resonance, stands out for the diagnostic method. Therefore, the use of antiparasitic drugs, as well as parasitic control in dogs and cats, are an important form of treatment. Neurotoxocariasis is not yet fully elucidated as a complication of toxocara infection, especially when it is associated with epilepsy. Thus, it is necessary that further studies are carried out in order to understand the effects of this parasitosis in patients of preschool and school age.